Plasma-induced poly(acrylic acid)-TiO2 coated polyvinylidene fluoride membrane for produced water treatment: Synchrotron X-Ray, optimization, and insight studies. (1st August 2019) - Chen, Xiujuan; Huang, Gordon; An, Chunjiang; Feng, Renfei; Yao, Yao; Zhao, Shan; Huang, Charley; Wu, Yinghui
Abstract: A super-hydrophilic, polyvinylidene fluoride (PVDF) membrane was obtained through plasma-induced poly (acrylic acid) (PAA) polymerization followed by titanium dioxide nano particles (TiO2 NPs) self-assembly for oily produced water treatment. Fractional factorial design method was applied to investigate the effects of experimental factors and their interactions on membrane modification. The mechanism of TiO2 NPs self-assembly was explored through synchrotron-based X-ray analyses and comprehensive membrane characterization. It was found that nano-TiO2 was immobilized onto the membrane surface through PAA layer without valence change. For the first time, the mechanism of nano-TiO2 immobilization was confirmed to be the coordination of Ti 4+ with carboxylic group. After modification, the TiO2 NPs were strongly and uniformly fixed on membrane surface, dramatically improving the hydrophilicity of the PVDF membrane surface. The permeation flux was increased more than four times, and the oil rejection rate was higher than 92%. The modified PVDF membrane has great potential in the application for various water-recovery systems, and this study provided a new insight into the nature of functionalized polymer membrane. Graphical abstract: Image 1 Highlights: A super-hydrophilic PVDF-PAA-TiO2 membrane was obtained. The modified membrane had 4 times higher permeate flux for produced water treatment. Factorial design was applied to investigate effects on membrane modification. The modification mechanisms were explored through synchrotron-based X-ray analyses.